CULTURAL AND CREATIVE INDUSTRIES - Diana Cristina Sava (Annals of the University of Oradea: Economic Science, 2016)
The creative economy has appeared as a new trend in the current economic reality, where information, knowledge and original creations as products of individual or work are represented as driving forces in the economic development. The main advantage brought up by the creative economy is its inexhaustible raw materials, the human capital with his creative mind. Nowadays, a company’s tangible assets or power of influence are no longer its most valuable possessions; there is something more valuable, more precisely, the intellectual capital, its human resources operating by their own will and leaving the company at the end of each working day. Any organisation, but mostly those conducting artistic or knowledge based activities must prove the ability to attract, retain and motivate valuable employees in order to exploit their arsenal and their ideas to be transformed into goods or services. Considering all the advantages of the new economic sector, a limit of the creative economy is the subjective way of assessing the created products and services’ value, the degree of satisfaction experienced by consuming such products being influenced largely by psychological factors. Creative economy presents itself as a novelty in the scientific economic field with its own terminology; thus referring to this economic sector it is required to address what is particular for it, such as: knowledge, creativity, creative industries, cultural industries, creative class, etc. This paper is a theoretical approach and it aims to present some of the specific concepts of the creative economy, more exactly the cultural industries and the creative industries. Also in order to achieve a better understanding and distinction I will present several classifications known in the literature of internationally recognised organisations such as UNESCO, UNCTAD, World Intellectual Property Organization, and others as well. Besides reviewing these approaches, the paper will show the author's own vision on the mentioned concepts.